Pemanfaatan Mikroskop dalam Menanggapi Fenomena Resistensi Antibiotik pada Bakteri Patogen - Desi Rahmasari; Devina Adira Azzahra; Hanayu Anindya Nareswari; Nasywarana Putri Panjaitan; Rizka Felithia; Elsa Oktavia Ramadhani; Liss Dyah Dewi Arini (Calory Journal Medical Laboratory Journal, 2025)
Antibiotic resistance has emerged as one of the most critical challenges in modern healthcare. Pathogenic bacteria that were once susceptible to antibiotics have developed survival mechanisms, making infections increasingly difficult to treat. Understanding and combating this issue requires advanced tools, with microscopy playing a pivotal role. Microscopes enable researchers to observe bacterial morphological changes, biofilm formation, and antibiotic-bacteria interactions at molecular levels. Various microscopy techniques – including light microscopy, electron microscopy, and fluorescence microscopy – have significantly contributed to both research and clinical diagnostics. Through a literature review approach, this article examines how microscopy facilitates antibiotic resistance studies and supports the development of more effective treatment strategies.